Antioxidant properties of tropical juices and their effects on in vitro hemoglobin and low density lipoprotein (LDL) oxidations - Ahmad Aufa, Zabidah; Kong, Kin Weng; Ismail, Amin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Antioxidant properties of tropical juices, namely bambangan (Mangifera pajang), cocoa (Theobroma cacao) pulp and guava (Psidium guajava) juices and their effects on in vitro hemoglobin and low density lipoprotein (LDL) oxidations were determined. Total phenolics and its compounds in selected juices were determined using Folin-Ciocalteu assay and high performance liquid chromatography (HPLC), respectively. Evaluation of antioxidant properties was done using in vitro assays namely as diphenyl-1-picrylhydrazyl (DPPH) scavenging, β-carotene bleaching (BCB), hemoglobin and LDL oxidation assays. Guava and bambangan juices had the highest and lowest of total phenolic content (TPC), respectively. Nevertheless, bambangan juice showed the greatest scavenging activity on DPPH radical. Furthermore, antioxidant activity (AA) in BCB assay was in the order of cocoa pulp (79%) > bambangan (76%) > guava (47%) juices. Interestingly, the highest inhibition of malondialdehyde (MDA) formation was exhibited by bambangan juice (0.31 µM MDA) in hemoglobin oxidation, while guava juice (0.27 µM MDA) in LDL oxidation systems. The study indicated that bambangan juice may have a potential to be introduced as functional foods product because of its antioxidant properties